Perlindungan Hak Privasi Anak Atas Pelanggaran Sharenting Oleh Orang Tua Di Indonesia - Permanasari, Ai; Hermanto Sirait, Yohanes (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2021)
Sharenting has become a phenomenon nowadays. Parents often share content in the form of photos or videos about their children through internet and social media. Unfortunately, the shared content is often detrimental to children's interests. This article aims to examine violations in the practice of sharenting and the importance of protecting children from the dangers of sharenting. This research was conducted normatively using primary, secondary, and tertiary legal materials. The statutory and conceptual approaches is used to answer the legal issues. The results showed that the practice of sharenting was carried out because of the lack of understanding from parents about the impact of sharenting on children and the lack of special rules governing violations of children's privacy by parents. There is not any guideline for children to understand what should be or should not be share on internet and social media. For this reason, a revision of legislation needs to be carried out to focus on prevention efforts and legal solutions for children and parents problem when the parents is the offenders.